Development of E-LKPD Based on Project Based Learning in IPAS Subjects to Improve Students' Critical Thinking Skills - Huda, Najmul; Waluyo, Edy; Marhamah, Marhamah (Sumber Belajar Sejahtera, 2025)
his study aims to develop an Electronic Student Worksheet (E-LKPD) based on Project-Based Learning (PjBL) for the Natural and Social Sciences (IPAS) subject to enhance the critical thinking skills of elementary school students. The research was conducted at SD Negeri 4 Pringgabaya, where traditional teaching methods using printed worksheets were found to be monotonous and less engaging, leading to decreased student motivation. The E-LKPD was designed using the LiveWorksheets platform, incorporating multimedia elements such as audio, video, and interactive questions to make learning more engaging and effective. The development process followed the Research and Development (R&D) method, simplified from Borg and Gall's model, and included stages such as needs analysis, planning, product development, validation, and testing. The E-LKPD was validated by material and design experts, with results indicating high validity and practicality. Effectiveness tests conducted in small and large groups showed significant improvements in students' critical thinking skills, as measured by pre-test and post-test scores using the N-Gain score. Student and teacher feedback also indicated high satisfaction with the E-LKPD, categorizing it as